Characterization of Photobacterium damselae subsp. damselae isolated from a spotted seal (Phoca largha) (Pinnipedia: Phocidae) stranded in Korea - Cha, Tae Seon; Park, Seon Young; Lee, Kyunglee; Park, Eun Jeong; Na, Jong Beom; Kim, Ye Bin; Lee, Keeman; Lim, Soojin; Uh, Namgyu; Jung, Ji-Youl; Kim, Byung Yeop; Kim, Bumkeun; et al. (Frontiers in Veterinary Science, 2025)
IntroductionPhotobacterium damselae subsp. damselae (PDD) is an emerging marine bacterial pathogen that infects marine animals and humans, causing fatal necrotizing fasciitis and histamine fish poisoning. Despite its clinical and ecological importance, the microbiological and genomic characteristics of PDD remain largely unknown.MethodsWe report the first case of systemic infection caused by PDD in a free-ranging spotted seal (Phoca largha) stranded in Korea. Histopathological and microbial examinations were performed, followed by genomic analysis of the isolated PDD strain GCUPdd. Histamine production capability and cytotoxic effects on human cells were also evaluated.ResultsPDD was identified as the presumptive cause of systemic infection in the seal. Genomic analysis revealed the presence of pPHDD-like plasmid and major virulence factors including damselysin, phobalysin, and phospholipase. Strain GCUPdd harbored a gene cluster for histamine production (histidyl-tRNA synthetase, histidine decarboxylase, and histidine-histamine antiporter) and exhibited significantly higher histamine-producing ability than the reference PDD strain. The strain also demonstrated cytotoxic effects on human cells.DiscussionAlthough the pathogenic role of PDD in pinnipeds remains unclear, this study highlights its zoonotic potential and the importance of monitoring PDD in marine environments. Our findings contribute to understanding risk factors for histamine fish poisoning and provide insights into microbial diversity in marine mammals, emphasizing the need for further surveillance concerning PDD pathogenicity and role in public health.